Land for housing the poor. Report of the United Nations seminar of experts on land for housing the poor, Tällberg and Stockholm, March 1983, organized by the United Nations Centre for Human Settlements (Habitat) in co-operation with the Ministry of the Interior, Finland and the Swedish Council for Building Research - (:unkn) unknown (My University, 1983)
Den Schwerpunkt der Veröffentlichung bilden die Empfehlungen der Experten an die Regierungen.Die Diskussionen der Veranstaltung sind kurz zusammengefaßt.Fast die Hälfte der Veröffentlichung umfassen vier Themenpapiere zu den Themen: Landerwerb und Unterkunft für die Armen, Methoden der Flächennutzung, Registrierung von Boden sowie Institutionen, Forschung und Ausbildung. difu
Keywords: Bodenpolitik; Armut; Flächennutzung; Bodenpolitik; Baugrund; Wohnungspolitik; Institution; Forschung; Ausbildung; Landesplanung; Politik; Boden